Implementation of advanced analytical methods into healthcare facilities in Turkey - Özdemir, Bilgi; Potančok, Martin; Štěpánek, Lubomír; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2021)
Technology is developing rapidly, with the development of technology, it develops and changes rapidly in the field of health. There are many technologies that play a role in this change, one of which is advanced analytical methods. There are many benefits that advanced analytical methods can and will add to the health system. In this process, the implementation of advanced analytical methods in healthcare facilities plays an essential role. This implementation process is quite complex. It has many components and all of them must be applied very carefully and effectively. The aim of this thesis is to discuss the process in detail and to create an exemplary implementation strategy.
Vedoucí práce: Martin Potančok
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses